Gynecologic radiology in fertility treatment: assessing tubal patency and ovarian reserve - Islam, Ali Haider M. Tohurul; Mostafa, Syeda Nazlee; Lovely, Nur A. Atia (International Journal of Research in Medical Sciences, 2024)
Background: A tubal patency test is a medical procedure that can help determine if a woman is having trouble conceiving due to blocked fallopian tubes. Fallopian tubal pathology is a primary risk factor for female infertility. Ovarian reserve is the number of healthy eggs in a woman's ovaries, and it’s a measure of the ability to have children. This study aimed to assess tubal patency and ovarian reserve in fertility treatment. Methods: In a retrospective cohort study, 75 women aged 18-40, treated from January to December 2023, were included. Fallopian tube patency was tested using hysterosalpingography, hysterosalpingo-contrast sonography, or laparoscopic chromopertubation. Results: Of 75 women, 19 (25.5%) were found to have at least one blocked fallopian tube. Unilateral blockage was more common than bilateral blockage, occurring in 12 out of the 19 cases (63.2%) compared to 7 out of 19 cases (36.8%). Mainly, blockages occurred near the opening of the fallopian tubes 86.2%. After adjusting for other factors, the presence of hydrosalpinx (odds ratio, OR, 13.323, 95% confidence interval, CI: 2.679-66.253, p=0.002) and myomas (OR 2.108, 95%CI: 1.008-4.409; p=0.048) were statistically significant factors associated with fallopian tube blockage. Conclusions: Gynecologic radiology is still of major relevance in fertility evaluation. The presence of uterine myomas and hydrosalpinges significantly increases the risk.